Performance of the renal resistive index and usual clinical indicators in predicting persistent AKI. Issue 1 (31st December 2022) - Fu, You; He, Cong; Jia, Lijing; Ge, Chen; Long, Ling; Bai, Yinxiang; Zhang, Na; Du, Quansheng; Shen, Limin; Zhao, Heling
Abstract: Background: Early recognition of persistent acute kidney injury (AKI) could optimize management and prevent deterioration of kidney function. The Doppler-based renal resistive index (RI) has shown promising results for predicting persistent AKI in preliminary studies. Here, we aimed to evaluate the performance of renal RI, clinical indicators, and their combinations to predict short-term kidney prognosis in septic shock patients. Method: We performed a retrospective study based on data from a prospective study in a single-center general ICU between November 2017 and October 2018. Patients with septic shock were included. Clinical indicators were evaluated immediately at inclusion, and renal RI was measured within the first 12 h of ICU admission after hemodynamic stabilization. Persistent AKI was defined as AKI without recovery within 72 h. A multivariable logistic regression was used to select significant variables associated with persistent AKI. The discriminative power was evaluated by a receiver operating characteristic curve analysis. Result: Overall, 102 patients were included, 39 of whom had persistent AKI. Renal RI was higher in the persistent AKI patients than in those without persistent AKI: 0.70 ± 0.05 vs. 0.66 ± 0.05; p = 0.001. The performance of RI to predict persistent AKI was poor, with an area under the receiver operating characteristic curve (AUROC) of 0.699 [95% confidence interval (CI) 0.600–0.786]. A clinical prediction model combining serum creatinine at inclusion and the nonrenal SOFA score showed a better prediction ability for nonrecovery, with an AUROC of 0.877 (95% CI 0.797–0.933, p = 0.0012). The addition of renal RI to this model did not improve the predictive performance. Conclusion: The Doppler-based renal resistive index performed poorly in predicting persistent AKI and did not improve the clinical prediction provided by a combination of serum creatinine at inclusion and the nonrenal SOFA score in patients with septic shock.